2008
DOI: 10.1021/jp8074173
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Surface-Supported Polypyrrole Capsules Using a Solidified Droplets Template Approach

Abstract: Three-dimensional polypyrrole microcapsules were prepared via chemical deposition of the polymer onto tetradecanol particles supported on solid substrates. The growing polymer deposited onto the particle surface yielded hemispherical containers that encapsulated the tetradecanol contents. Mixing the tetradecanol with other chemical species, like fluorescent dyes, allowed the entrapment of these species within the containers. It was shown that by controlling the temperature, one could reversibly melt and solidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…This type of emission spectra can be expected for pyrene entrapped in the polymer during oxidative formation of the matrix, and explained by positively charged polymer chains leading to separation of pyrene molecules and distribution within the nanostructure e.g. .…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This type of emission spectra can be expected for pyrene entrapped in the polymer during oxidative formation of the matrix, and explained by positively charged polymer chains leading to separation of pyrene molecules and distribution within the nanostructure e.g. .…”
Section: Resultssupporting
confidence: 76%
“…This effect is expected for the change of the polymer properties – increasing hydrophilicity of the environment is promoting aggregation of pyrene molecules, which in turn results in exposed emission from the excimers. A similar effect was observed for polypyrrole microcapsules containing pyrene molecules in the solution inside the structure ,. Thus the nanoPPyNO 3 ‐Py is an excellent candidate to be wireless optical solution redox potential probe.…”
Section: Resultsmentioning
confidence: 99%
“…4e). While PPy nanoparticles demonstrated that stretching bands at 1472 and 1550 cm À1 due to the pyrrole ring [27], a shoulder band at 1690 cm À1 assigned to part of the oxidized pyrrole ring [28], two bands at 1032 and 1301 cm À1 attributed to CÀN stretching bands [29], and stretching bands at 923 and 1202 cm À1 generated by doped PPy [30]. Note that a small shoulder band at 740 cm À1 appeared in spectra of PPy nanoparticles, indicating that a small amount of 2,4-diaminodiphenylamine has copolymerized with pyrrole, as shown in Scheme 1.…”
Section: Ft-ir Spectramentioning
confidence: 99%
“…The peaks at near 1500 cm −1 and 1450 cm −1 could be attributed to stretching vibration of C−N and C−C on the pyrrole ring. The absorption peak at 1550 cm −1 corresponds to the C=C stretching vibration bond of the pyrrole ring [ 33 ]. These characteristic peaks were consistent with the characteristic peaks of WPPy.…”
Section: Resultsmentioning
confidence: 99%